Energy Pricing Policies for Inclusive Growth in Latin America and the Caribbean - Beylis, Guillermo; Cunha, Barbara (Washington, DC: World Bank, 2017)
Government strategies for setting energy prices are not uniform across the Latin America and the Caribbean (LAC) region—or even across fuels. Instead, they cover a full spectrum, ranging from discretionary price-fixing at one end to pure market-based approaches at the other. In between is a wide variety of other schemes such as price stabilization funds, import or export parity pricing, price smoothing through tax levels, and targeted direct price subsidies or vouchers. Governments in the LAC region, however, tend to be small as measured by government revenues as a percentage of GDP. So their limited government resources have to be used wisely and be better targeted to the poor and vulnerable. Although energy subsidies are an inefficient policy tool for protecting the welfare of the poor, energy price increases can have a big impact on these households.